Способ нанесения полимерного покрытия с использованием ультразвукового воздействия - Клименов В. А. Василий Александрович; Бузник В. М. Вячеслав Михайлович; Борозна В. Ю. Вячеслав Юрьевич; Зайцев К. В. Константин Викторович; Ковалевская Ж. Г. Жанна Геннадьевна
опубл. 10.11.12